The Sales Channel Strategies of Finnish Building Material Manufacturers for Entering Russian Market - Vuorenmaa, Pauliina (My University, 2006)
The aim of this research is to study sales channel strategies of Finnish building material manufacturers for entering Russian market. The fundamental research question is: “How and why certain type of sales channel strategies have been developed when operating in Russia?” The theoretical and empirical objectives guide the study process. First, the possible sales channel options when entering Russian market are familiarised with. In addition, variables affecting channel strategy in Russia are evaluated. The theoretical framework combines the factors impacting the channel strategy (channel length, density and type of intermediaries). Factors are divided into two blocks: internal and external factors. Internal factors include company specific factors and control related variables. Again, external factors refer to aspects, which the company cannot influence. Those are for example economical development, legal framework or competition in the target market. Two case companies, their sales channels’ development and factors impacted the development will be presented in the empirical part. The most suitable methodology was argued to be qualitative case study method instead of quantitative. This is due to the novelty of research subject. The reliability and validity are carefully examined. Due to the nature of case study research one should be cautious about generalization beyond the companies studied. Discussion between theory and data is done in the end of the study. Also theoretical and managerial implications are discussed. Last, some future study proposals are suggested.
Keywords: Sales channel strategies; Russia; internationalisation; building materials; fi=Markkinointi|en=Marketing|; fi=Kansainvälisen yritystoiminnan koulutusohjelma|